Miejsce i kontekst odniesień do pism św. Augustyna z Hippony w "Liber de divinis officiis" Ruperta z Deutz OSB - Pałęcki, Waldemar (Vox Patrum, 2024)
Medieval theologians, in the name of the principle of unanimity (unanimitas), referred in their works to the writings of the Church Fathers to give credibility to their message. An example of this are treatises explaining the liturgy allegorically, including the Liber de divinis officiis by Rupert of Deutz OSB (1075/76-1129). The author’s research goal is to indicate those places where Rupert of Deutz directly refers in his work to the writings of St. Augustine and gives them a new context in the Roman liturgy he explained. The structure of the present analysis was determined by the places of references to St. Augustine in the work of Rupert of Deutz, who made direct use of the following writings of St. Augustine: De civitate Dei, De doctrina christiana, De fide et symbolo, Enarrationes in Psalmos, Epistula 265, In Iohannis euangelium tractatus. The article uses a historical-critical method, supplemented with contextual and descriptive analysis. As a result of the analyses, it was found that Rupert of Deutz sometimes interprets the thought of St. Augustine slightly differently (e.g. the interpretation of the dimensions of the cross) or uses the arguments of the Bishop of Hippo for different theological content than in his works (e.g. explaining the octave of Easter). To sum up, the article shows the reception of the teachings of St. Augustine in the Middle Ages on the example of Liber de divinis officiis by Rupert of Deutz in relation to the explanation of the Roman liturgy.